Comparative Analysis for Churn Prediction Model in Telecom Industry - Pund, SP; Deshmukh, SN (International Journal of Computer Sciences and Engineering, 2025)
Churn prediction is the demanding field today and to stand in the market place or to capture market and for profit maximization churn prediction is very useful. Churn defines the customers switching another company, this is because the market strategy is rapidly changing. Other competitive companies give something new to the customers with low cost. Hence customers change their service provider very fast. Whereas retaining old customers is easy than gaining new customers. Retaining the customers by giving more offers is easy. The goal of this paper is to predict customer churn which will help to retain them. Many organizations feel the data base containing old customer information effectively predicts or generates the outputs. Data mining plays a vital role in churn prediction. Comparative study of the various classification algorithm can be done to give more accurate results.